British foreign policy from 1815 to 1933 - Edwards, William (London, 1934)
This book has been written to help students who are taking the latest period of British History for the Higher Certificate, Scholarship and University Examinations. But the author hopes that his attempt to trace the development of British Foreign Policy from 1815 to 1933 will prove helpful to others who are interested in current history. He has therefore carried the story beyond the period usually set for examinations; he has tried to put in their proper setting questions which to-day are pressing for solution; and to show the great importance of the struggle between Nationalism and Internationalism out of which present problems of Foreign Policy have arisen.
Keywords: Foreign policy - Great Britain -1915 -1933